ECONOMIC AND TECHNICAL ASPECTS OF CONSTRUCTION WIND TURBINES IN THE RUSSIAN FEDERATION - A. Borozdin (Вестник университета)
Wind energy development can be the development of innovative ways to use effective technologies of energy production based on renewable sources of energy in the development of new oil fields in Russia. The construction of wind farms will have a significant impact on the development of the oil and pipe industry.